Intermediate texts in Marcela de Juan’s translation of classical Chinese poetry - Jiawei, Wang (Sinología hispánica. China Studies Review, 2021)
Marcela de Juan (1905-1981), Spanish sinologist and polyglot translator, was pioneer in Spain of the diffusion of Chinese culture from 1928 until her death in 1981. However, her translations of Classical Chinese poetry are little studied till today. Through a comparative analysis that includes a simple statistical measurement, we have found that Marcela de Juan belongs to the line of translators who chose, as usual until the 1970s, to use French intermediate translations. Several examples of her practice in the poetic translation are presented in this text, and some of the reference French versions are referred to. Without detracting from the real interest of these versions of Marcela de Juan for their Spanish-language readers, and the influence these versions exerted in the introduction of Classical Chinese literature to Spain on its historical context.